2002
DOI: 10.1590/s1516-35982002000600017
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento de Carcaça, Mensurações e Peso de Cortes Comerciais de Cordeiros Santa Inês e Bergamácia Alimentados com Dejetos de Suínos em Confinamento

Abstract: RESUMO -Foram utilizados 21 cordeiros das raças Santa Inês e Bergamácia, confinados por um período de 75 dias, sendo alimentados com dietas contendo 24% de dejetos de suínos, na forma de biju (dejeto obtido pela raspagem e varredura do piso das baias de crescimento e terminação) ou dejeto peneirado seco -DPS (dejeto obtido através da peneiração da parte sólida do material contido na lâmina d'água e na água da lavagem das baias). Os animais foram abatidos aos 210 dias de idade, sendo determinados o peso e o ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
18

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 2 publications
(3 reference statements)
1
5
0
18
Order By: Relevance
“…Oliveira et al (2002) studied Santa Inês and Bergamácia lambs finished in feedlot and fed diets containing residues from pig farming, similarly to the present study, and found no treatment effect on hot carcass weight (23.3 kg), hot carcass yield (53.3%), cold carcass weight (23.0kg), cold carcass yield (52.6%) or cooling losses (1.20%).…”
Section: Resultssupporting
confidence: 81%
“…Oliveira et al (2002) studied Santa Inês and Bergamácia lambs finished in feedlot and fed diets containing residues from pig farming, similarly to the present study, and found no treatment effect on hot carcass weight (23.3 kg), hot carcass yield (53.3%), cold carcass weight (23.0kg), cold carcass yield (52.6%) or cooling losses (1.20%).…”
Section: Resultssupporting
confidence: 81%
“…Large-and medium-framed lambs showed values of 1.41% and 1.77%, respectively. These losses were higher compared with 1.20% found by Oliveira et al (2002) with Santa Ines lambs finished in feedlots and slaughtered with a live weight of 43.7 kg.…”
Section: Resultsmentioning
confidence: 57%
“…Landim et al (2007) found values of 1.74, 0.30, 1.02 and 1.43 kg for the cuts ham, loin, shoulder and rib, respectively, in Santa Ines sheep slaughtered at 30 kg. Oliveira et al (2002) showed averages for shoulder, loin and leg of 1.67, 0.91 and 3.08 kg, respectively, in Santa Ines lambs fed pig manure.…”
Section: Resultsmentioning
confidence: 92%